ENGLISH LANGUAGE TEACHING THROUGH COMMUNICATIVE APPROACH: ENGLISH LANGUAGE TEACHING THROUGH COMMUNICATIVE APPROACH - Khojametova, Gulnara (Журнал иностранных языков и лингвистики, 2025)
The Communicative Approach (CA) to language teaching has gained significant popularity over the past few decades, emphasizing real-world communication and the functional use of language. This approach represents a shift from traditional, grammar-centered methods, focusing instead on the use of language in social contexts to express meaning. It was developed as a reaction to the limitations of the Audio-lingual Method and Grammar-Translation Method, which were primarily concerned with rote memorization of rules and patterns, rather than actual communication skills. The Communicative Approach seeks to ensure that learners develop the ability to communicate effectively and meaningfully in real-life situations.